Try 3a2 - 12b2 = 3(a2 - 4b2) = 3(a - 2b)(a + 2b)
2006-10-19 06:51:45
·
answer #1
·
answered by F.G. 5
·
2⤊
0⤋
Complete factors of:
3a² - 12b² = 3(a² - 4b² )
= 3(a + 2b)(a - 2b).
2006-10-19 06:53:23
·
answer #2
·
answered by quidwai 4
·
2⤊
0⤋
You had the first step right...factor out the 3 to get:
(3)*(a^2 - 4b^2)
Now the second factor is the difference of two squares, so take the square root of both terms and get:
(3)*(a+2b)*(a-2b)
(You're earlier mistake was not taking the square root of the 4)
2006-10-19 06:52:04
·
answer #3
·
answered by Anonymous
·
5⤊
0⤋
3 is a common to both so
= 3(a² - 4b²)
= 3(a-2b)(a+2b)
when u expand u get
3(a² +2ab-2ab-4b²)
3(a² -4b²)
= 3a² -12b²
2006-10-19 07:39:02
·
answer #4
·
answered by Venkatesh V S 5
·
0⤊
0⤋
3a^7 - 48a^3 The GCD of this expression is 3a^3. factor it out. 3a^7 - 48a^3 = 3a^3(a^4 - sixteen) a^4 - sixteen = (a^2)^2 - 4^2 that's interior the style x^2 - y^2 = (x + y)(x - y) a^2 - sixteen = (a^2 + 4)(a^2 - 4) a^2 - 4 might properly be further factored a^2 - 4 = (a + 2)(a - 2) answer : 3a^7 - 48a^3 = 3a^3(a^2 + 4)(a + 2)(a - 2)
2016-10-02 11:26:20
·
answer #5
·
answered by ? 4
·
0⤊
0⤋
Take the 3 out. You are left with
3(a^2 - 4b^2) = 3(a^2 - (2b)^2) = 3(a - 2b)(a + 3b)
2006-10-19 07:03:36
·
answer #6
·
answered by Dr. J. 6
·
1⤊
0⤋
3a² - 12b²
3(a^2-4b^2)
3(a+2b)(a-2b)
2006-10-19 08:23:24
·
answer #7
·
answered by yupchagee 7
·
0⤊
0⤋
the square root of 4 is 2 not 4:
3(a+2b)(a-2b)
2006-10-19 07:18:14
·
answer #8
·
answered by csulbalgebra 2
·
1⤊
0⤋
3(a^2 - 4b^2) = 3(a-2b)(a+2b)
2006-10-19 06:53:06
·
answer #9
·
answered by Anonymous
·
2⤊
0⤋
3a^2-12b^2=
3(a^2-4b^2)=
3[(a-2b)(a+2b)]
2006-10-19 10:47:51
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋
3a² - 12b²
3(a² - 4b²)
3(a - 2b)(a + 2b)
- - - - - - - -s
2006-10-19 07:22:42
·
answer #11
·
answered by SAMUEL D 7
·
1⤊
0⤋